Employee Job Satisfaction at a Barbershop: Kepuasan Kerja Karyawan di Tempat Cukur Rambut - Indradi, Syahnurofi Reno; Affandi, Ghozali Rusyid (Indonesian Journal of Education Methods Development, 2023)
This study aims to determine and provide an explanation of the job satisfaction of employees of CV El. Capitano Sidoarjo. This research method is descriptive quantitative with the subject of all employees CV. El Capitano Sidoarjo, totaling 67 employees. Determination of the subject using a saturated sampling technique where the researcher uses the entire existing population. The variable in this study is job satisfaction. The data collection in this study used a psychological preparation scale, namely the Likert scale for the job satisfaction variable made by the researcher. Analysis of the data in this study using Microsoft Excel. The results of data analysis show that job satisfaction of employees at CV El Capitano Sidoarjo is in the medium category with a percentage value of 57% indicating that employees of CV. El Capitano Sidoarjo is satisfied with the work they do.